2003
DOI: 10.1128/jcm.41.11.5215-5223.2003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Genetic Differences between Mycobacterium avium subsp. paratuberculosis Type I and Type II Isolates

Abstract: A combination of representational difference analysis and comparative DNA sequencing revealed that four type I (sheep) isolates of Mycobacterium avium subsp. paratuberculosis were differentiated from nine type II (bovine) isolates by the presence of an 11-bp insertion in a novel M. avium subsp. paratuberculosis-specific region of genomic DNA. Further, our studies show that M. avium subsp. paratuberculosis type I isolates contain three type-specific loci that are missing in M. avium subsp. paratuberculosis type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 30 publications
1
38
0
1
Order By: Relevance
“…1) ing from C strains of M. avium subsp. paratuberculosis are in agreement with and expand upon findings from a representational difference analysis-based study that identified three loci missing from type II (C type) strains (9). The 233-bp locus they identified as pig-RDA10 (AY266300) forms part of the 16-kb region we called LSP A 18.…”
Section: Discussionsupporting
confidence: 73%
“…1) ing from C strains of M. avium subsp. paratuberculosis are in agreement with and expand upon findings from a representational difference analysis-based study that identified three loci missing from type II (C type) strains (9). The 233-bp locus they identified as pig-RDA10 (AY266300) forms part of the 16-kb region we called LSP A 18.…”
Section: Discussionsupporting
confidence: 73%
“…paratuberculosis. The presence of LSP P 12, a previously described 19-kb island (8,23), was also highly predictive of the identification of M. avium subsp. paratuberculosis.…”
Section: Discussionmentioning
confidence: 85%
“…avium strains were then tested across the extended panel of 383 M. avium complex isolates. Since LSP P 14, which includes but is not restricted to a known 38-kb island (24), and LSP P 12, a 19-kb sequence (8,23), were previously postulated to be of potential diagnostic utility, we tested each of these LSPs with two and three different sets of primers targeting distinct loci, respectively. Primer sequences for each of the LSP P s tested are listed in (23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediately, a correlation was noticed between strain type and ease of isolation, as the S strains were notoriously difficult to grow. Greater genetic diversity was later identified, particularly between S and C strains, as small and large genomic deletions and insertions and single nucleotide polymorphisms were found (13,(24)(25)(26). The so-called S and C strains probably represent the extremes of a taxon; a continuum may exist, and this will be determined when representative genomes have been sequenced and annotated.…”
mentioning
confidence: 99%